Women students performing 'gymnasium drill' with 'wands' - Frank Aston::::::photographer::: (1916)
Women students in gymnasium uniforms (sailor blouses, bloomers and stockings) using 'wands' during 'gymnasium drill.' Taken outdoors, next to one of the main buildings. Published in the 1915-16 Bulletin of Information (course catalogue). A finger or thumb print is visible in the lower left corner of the print.